Pendidikan Antikorupsi Dalam Kurikulum Pendidikan Tinggi: Studi Korelasi Pada Sikap dan Perilaku Antikorupsi Civitas Akademika ITEKES Bali - Asthadi Mahendra Bhandesa; I Made Sudarsana; I Putu Agus Endra Susanta; I Putu Gede Sutrisna; Ida Bagus Ardhi Putra; Komang Ayu Masri (Jayapangus Press, 2023)
The anti-corruption education is a process of learning and forming behavior held in Higher Education to prevent corrupt behavior and criminal acts. The purposes of this study were (1) to analyze the implementation of anti-corruption education, (2) to identify the knowledge about anti-corruption, (3) to identify the anti-corruption attitudes and behaviour, (4) to determine the correlation between knowledge with anti-corruption attitudes and behavior in the academic community of ITEKES Bali. This research employed mixed methods research with a sequential exploratory design. Data were collected qualitatively through interviews and documentation studies on the curriculum of Higher Education and study programs at ITEKES Bali. Moreover, the data were collected quantitatively with google form about the knowledge, anti-corruption attitudes and behaviour of the academic community.The findings indicated that (1) the implementation of anti-corruption education at ITEKES Bali in the form of 2 SKS credits of Anti-Corruption Education courses in each study program, the introduction of anti-corruption values during the PKKMB period, and Anti-Corruption Education Lecturer training activities as well as in other forms of activities such as research and seminars attended by lecturers and students, preparation of anti-corruption education modules, anti-corruption campaigns on social media; (2) the knowledge of ITEKES Bali Academic Community on anti-corruption was still quite good; (3) the attitudes and behavior of the respondents fall into the very good category; (4) the correlation coefficient between Anti-Corruption Education (x) and Anti-Corruption Attitudes and Behavior (y) was (r) = 0.739 with a significance of 0.002. It could be concluded that the correlation between the two variables is significant (0.002 <0.05) with a positive and strong correlation. It is suggested to increase the quantity and quality of anti-corruption knowledge, and the improvement of anti-corruption attitudes and behavior.